DESA WISATA NEPO DI KABUPATEN BARRU: DESA BUDAYA YANG RELIGIUS - Umi Kalsum (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
This article discusses the potential of the Nepo tourism village in Barru Regency. Nepo Tourism Village is one of the villages that has the nickname Little Habibie village which offers cultural and culinary tours for tourists. Unfortunately, many tourists are not familiar with Nepo Tourism Village, and what attractions can be done there, including the available accommodation facilities. Qualitative methods are used in this article, because they are limited to describing, not measuring using numbers as quantitative. The potential of Nepo Tourism Village is its culture and people who are religious, the characteristics of a pious society or in the Nurcholish Madjid language, civil society. However, Nepo Tourism Village still has challenges to increase accommodation in the form of homestays, as well as facilities and infrastructure, including maintaining the security and safety of tourists visiting Nepo Tourism Village.